PENGARUH LINGKUNGAN KERJA, PELATIHAN DAN PENGEMBANGAN SUMBER DAYA INSANI TERHADAP ETOS KERJA KARYAWAN KOPPONTREN AUSATH BLOKAGUNG KARANGDORO TEGALSARI BANYUWANGI - jazil, ahmad syafiul (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The purpose of this study was to determine the effect of the work environment (X1), training (X2) and human resource development (X3) employees of Koppontren Ausath Blokagung Karangdoro Village, Tegalsari District, Banyuwangi Regency partially and simultaneously on work ethic (Y). The writing of this scientific article uses quantitative research methods using an explanatory research approach. The sample in the study amounted to 35 respondents. The results of the research are positive and significant work environment (X1), training (X2) and human resource development (X3) employees of Koppontren Ausath Blokagung Karangdoro Village, Tegalsari District, Banyuwangi Regency partially and simultaneously affect work ethic (Y). It is concluded that the research is able to answer the hypothesis which states that the variables of work environment (X1), training (X2) and human resource development (X3) employees of Koppontren Ausath Blokagung Karangdoro Village, Tegalsari District, Banyuwangi Regency have partial and simultaneous effect on work ethic (Y).